Этнический состав и этническая структура общества: попытка уточнения понятий - Нельга, А. (Социология: теория, методы, маркетинг, 2009)
The notion of ethnic structure of society per se have been first singled out the “charger” of concepts of national and ethnic structures of society only at the end of 90th of ХХth century. Theoretical clearing up of the problem is complicated by unsettled state of concept-category apparatus, namely identifying of concepts of ethnic structure and ethnic composition of society, interpretation the nation as an ethnic phenomenon and so on. The ethnic structure of society is one of types (substructures) of its social structure. Consequently, the reasonable solution of society ethnic structuring ques tions is to be carried out on methodological principles of social structuring in general. The author uses as a basis Anthony Giddens’ determination which assumes the social structure of society as a gnosiological construct. However, the author underlines, that this structure is not merely a product of consciousness, but is the phenomenon based on relations communications between elements of empirically fixed ontological reality, that is the social structure of society. Therefore determination of the social structure notion must represent its pluralistic essence and the distinction between social struc ture and composition of society. On these principles, the analysis of ethnic structure of society should be deepened up to the level of its substructures, including ethnic structure. Particularly, one can select its mere components brought into correlation with tasks of political nation building.